PENGARUH KENIKMATAN MAKANAN DAN KUALITAS PELAYANAN TERHADAP MINAT BELI SATE PADANG KUPAK - AMRIL ANAS (LP2MTBM MAKARIOZ, 2019)
Consumer buying interest are nfluenced by the taste of food and service quality factor. Small shop must be able to choose a strategic taste of food and provide good quality service towards consumers to beat others in competition. Taste of food as a potential strategic weapon to beat competitors.Quality of service as an important factor toinfluence consumer buying interest. Strategic taste of food andgood service are able to increase consumer buying interest on the product selling. The purpose of this study is to find out or analyze the influence of taste of food and quality of service towards consumer buyinginterest at Sate Padang Kupak. This research was conducted at Sate Padang Kupak.The type of research used is descriptive quantitative research.The results shows that the taste of food variable and quality of service make a positive and significant influence both partially and simultaneously towards consumer buying interest at Sate Padang Kupak. 37,1% ofR Square value shows that 37,1%ability of taste of food (X1) and quality of service(X2) variablesare able to influence consumer buyinginterest (Y) at Sate Padang Kupak while the remaining62,9% are the influence of other independent variables that are not explained or not analyzed by researcher in this study such as product quality, product distribution or prices variables.